Rancang Bangun Sistem Pembuangan Air Otomatis Pada Kapal Pompong Nelayan Menggunakan Tenaga Surya Berbasis Internet Of Things - Hardinata, Danil; Asri Yana Vita, Devi; Yulfaturrahmi, Lusya (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2024)
The automatic water disposal system on fishing boats is an innovative solution to overcome the problems often faced by fishermen related to water leaks and manual water disposal which requires a lot of time and effort. This research aims to design and build an automatic water disposal system on a fishing boat by utilizing solar power as a renewable energy source and based on the Internet of Things (IoT) to enable remote monitoring and control. This system uses a water level sensor to detect the water level inside the ship and activates the water pump automatically when the water level reaches a certain point. Solar power is used as the main energy source to power the system, making it more environmentally friendly and reducing dependence on fossil fuels. Integration with IoT allows fishermen to monitor vessel conditions and control the system via smartphone, thereby increasing safety and operational efficiency. Data collection methods used in this research include interviews with fishermen, field observations, and literature studies related to the technology used. Meanwhile, the system development method uses the Agile Method, which allows fast iteration, close collaboration with end users (fishermen), and adjustment to changes during the development process. The Agile method ensures that the system developed meets the real needs of fishermen and can be adapted to changing field conditions. The research results show that the automatic water disposal system can work effectively, efficiently and safely in removing water that enters the ship. This system helps fishermen save time, energy and operational costs by reducing the need to drain water manually. Apart from that, the use of solar power as an energy source also contributes to efforts to preserve the environment by reducing carbon emissions from burning fossil fuels. Thus, this system offers a profitable solution for fishermen and the environment.